A Legal Review of Sanctions for Illegal Logging Violations Based on Forestry Law - Rini Armianti Berutu; Ramsul Nababan (Badan Penerbit STIEPARI Press, 2025)
This study aims to examine the application of sanctions for illegal logging violations based on the Forestry Law, with a case study focused on Kaban Tengah Village, STU Jehe Sub-district, Pakpak Bharat Regency. This research employs an empirical normative legal method using a case study approach. The study was conducted in Kaban Tengah Village, STU Jehe Sub-district, Pakpak Bharat Regency. The data utilized in this research consist of primary and secondary data. Data collection techniques include direct interviews, field observations, and documentation. The data analysis technique used is qualitative, comprising data reduction, data presentation, and data verification or conclusion drawing. The results indicate that illegal logging activities have complex and detrimental impacts on both the community and the environment. These include ecological damage such as increased landslide risk and loss of forest cover, disruption to village infrastructure, particularly main connecting roads, and economic losses due to damaged agricultural land and hampered crop distribution. Based on the findings and legal review of sanctions for illegal logging violations in Kaban Tengah Village, it was found that law enforcement against illegal logging activities has not been effectively implemented as stipulated in the Forestry Law. Law enforcement at the local level remains formalistic and has not addressed the root of the problem due to several challenges, including limited human resources, inadequate monitoring facilities, poor infrastructure, and lengthy and bureaucratic legal processes. Furthermore, the low level of legal awareness among the community and the involvement of local residents in illegal logging practices further complicate enforcement efforts, posing significant challenges for law enforcers in reviewing sanctions against illegal logging perpetrators in Kaban Tengah Village.